Analysis of the Balance of Income and Expenditure of Fishermen in Tatombuli Village, Bonegunu District, North Buton Regency - Ziati, Ziati; La Ode Alwi; Hidrawati, Hidrawati (International journal of technology and education research, 2025)
This research aims to determine the balance of income and expenditure of fishing households in Tatombuli Village, Bonegunu District, North Buton Regency. The population in this study were all fishermen in Tatombuli Village, Bonegunu District, North Buton Regency, totaling 42 people. The sample was determined using the census technique, namely taking the entire population as a sample. The data was analyzed quantitatively using income, household consumption expenditure and savings function. The results of the research show that (1) The average income of fishermen in Tatombuli Village from fishing is IDR26,561,080/year, (2) The average household consumption expenditure of fishermen in Tatombuli Village is IDR20,145,738/year, which includes food expenditure amounting to IDR13,814,881/year and non-food expenditure amounting to IDR6,330,857/year, and (3) Household economic balance, namely surplus or income greater than consumption expenditure with savings of IDR6.415,342/year, which means that the household Fishermen are able to finance all household expenses from the income they earn